A total viewshed approach to local visibility in the Chaco World. (August 2018) - Dungan, Katherine A.; White, Devin; Déderix, Sylviane; Mills, Barbara J.; Safi, Kristin
Abstract : Abstract : The Chacoan great houses and great kivas of the U.S. Southwest are monumental, both in their scale and in conveying meaning. Visibility is key to understanding how and by whom that meaning was experienced. Although often discussed in Chaco studies, visibility has been infrequently tested. Here, the authors consider 430 great house and great kiva locations, and evaluate their visibility within their local landscapes. Using a total viewshed approach, they provide new evidence to suggest that great houses, but not great kivas, were often placed to be highly visible to individuals in the surrounding landscape. These patterns may speak to the social and physical properties of the structures.